Pengoptimalan Lahan Pekarangan Sebagai Upaya Ketahanan Pangan Pada Kawasan Rumah Pangan Lestari - Robby Sandhi Dessyarti; Apriyanti Apriyanti; Metik Asmike; Novi Dwi Lestari; Risma Choirunisa (STMIK Royal, 2022)
Abstract: Klangon Village is a hilly area which is located on the slopes of Mount Pan-dan and is in the Madiun Regency area which is one of the partner villages of Universitas PGRI Madiun. Klangon Village has an organization in the field of agriculture, namely the “Karya Putri Tani” farmer group. The organization received funding aimed at the development of a sustainable food housing area (KRPL) but it was not yet optimal and running smoothly. The existence of these problems became the basis for conducting yard optimization activities for food security in the area of sustainable food houses. The methods used in the activities include mentoring and training in the form of demonstrations. Hope in this program can meet the needs, food security, and nutrition of the family which will ultimately improve the welfare of the community. The results achieved in the program are that the target group can implement a sustainable food home area in the form of